Experimental study of the dynamics of morphological changes in the rat testum under chronic influence of cadmium chloride - Nefodova , O.O.; Hruzd , V.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Cadmium-associated disorders of the functional activity of the hypothalamic-pituitary-gonadal system in men are manifested by a violation of both the hormonal regulation of the reproductive system and the functioning of the epitheliospermatogenic layer of the seminal glands, causing pathological changes in both the quantitative and qualitative composition of sperm. The aim of the work was to reveal the specifics of the effect of chronic administration of cadmium chloride on the state of the rat testicle with a comparison of the effect of isolated administration of cadmium chloride on the morphofunctional state of the testicle in a chronic experiment on rats. Methods. Histological and morphogistometric study. The results. In order to fulfill the set goal and ensure a correct comparative analysis of the obtained results of exposure to cadmium chloride during experimental studies, we conducted a study of the characteristics of testicular morphogenesis in a control group of young male rats of puberty age in comparison to the group isolated exposure to cadmium chloride. Operative slaughter of animals to obtain samples took place on the 14th, 20th and 30th days of the experiment. After anesthesia, the testicles were removed, weighed, measured for the protocol and subject to fixation for further histological examination. Analyzing weight indicators, we determined the relative weight of the testicle itself to the weight of the animal, which is more informative material for comparison between groups. Result. It has been experimentally proven that the influence of cadmium chloride causes an increase in massometric parameters of the testicle by 12-13% compared to the control (the reliability of the difference was p≤0.05) at all times of the study. At the same time, in the experimental group exposed to cadmium chloride, the weight loss of experimental animals was determined. Calculation of the testicular mass index showed that the testicular mass index was 1.4 times higher than the control indicators in all studied terms. Chronic exposure to cadmium chloride led to a significant thickening of the testicle’s protein shell, its stratification, and an increase in the diameter of blood vessels and a high level of blood filling. Exposure to cadmium chloride at all study periods led to an increase in the average diameter of the testicular seminiferous tubules from 13% to 15% (p=0.05) and significant swelling of the interstitial space of the testicular stroma in an experiment on rats. Exposure to cadmium leads to a change in the histological structure of the testicular parenchyma, namely the structural and functional unit of the testicle - the convoluted seminiferous tubule. In 68% of the examined sections of the testicular parenchyma, the thinning of the inner layer of the tubule shell and its stratification into separate strands with the expansion of the inner space of the tubule and the decrease in the number of primary spermatocytes were determined.